Functional imaging of mitochondria in retinal diseases using flavoprotein fluorescence - Chen, Andrew X; Conti, Thais F; Hom, Grant L; Greenlee, Tyler E; Raimondi, Raffaele; Briskin, Isaac N; Rich, Collin A; Kampani, Reecha; Engel, Robert; Sharma, Sumit; Talcott, Katherine E; Singh, Rishi P (Eye (London), 2021)
Mitochondria are critical for cellular energy production and homeostasis. Oxidative stress and associated mitochondrial dysfunction are integral components of the pathophysiology of retinal diseases, including diabetic retinopathy (DR), age-related macular degeneration, and glaucoma. Within mitochondria, flavoproteins are oxidized and reduced and emit a green autofluorescence when oxidized following blue light excitation. Recently, a noninvasive imaging device was developed to measure retinal flavoprotein fluorescence (FPF). Thus, oxidized FPF can act as a biomarker of mitochondrial dysfunction. This review article describes the literature surrounding mitochondrial FPF imaging in retinal disease. The authors describe the role of mitochondrial dysfunction in retinal diseases, experiments using FPF as a marker of mitochondrial dysfunction in vitro, the three generations of retinal FPF imaging devices, and the peer-reviewed publications that have examined FPF imaging in patients. Finally, the authors report their own study findings. Goals were to establish normative reference levels for FPF intensity and heterogeneity in healthy eyes, to compare between healthy eyes and eyes with diabetes and DR, and to compare across stages of DR. The authors present methods to calculate a patient's expected FPF values using baseline characteristics. FPF intensity and heterogeneity were elevated in diabetic eyes compared to age-matched control eyes, and in proliferative DR compared to diabetic eyes without retinopathy. In diabetic eyes, higher FPF heterogeneity was associated with poorer visual acuity. In conclusion, while current retinal imaging modalities frequently focus on structural features, functional mitochondrial imaging shows promise as a metabolically targeted tool to evaluate retinal disease.